Face to Face: an Episode from the History of one Travel Sketch - Glushakov, Pavel (Literatūra, 2025)
The article is devoted to the history of Viktor Nekrasov’s travel essay “On Both Sides of the Ocean”. Immediately after its publication in the journal “Novy Mir” (No. 11–12, 1962), this work aroused the displeasure not only of official critics but was also condemned by the head of the Party and the government, Nikita Khrushchev, at the Plenary Session of the Central Committee of the Communist Party of the Soviet Union CPSU (June 1963). The reasons for such an attack on the essay, which depicts real facts and phenomena observed by the narrator, lie not only in the sphere of ideology but also represent a manifestation of the literary struggle of the time. Nekrasov’s travel essay destabilized the existing cultural situation – the privilege of certain ‘authorized’ authors to present the Soviet reader with ‘other worlds’ and to express their views on life beyond the homeland. It refers to the book “Face to Face with America”, published in 1960, written by a group of journalists, writers, and statesmen, and awarded the highest distinction – the Lenin Prize. The article publishes for the first time an unsent explanatory letter by Viktor Nekrasov addressed to Nikita Khrushchev.
Keywords: В. Некрасов; Н. Хрущев; очерк; идеология; «Оттепель»